Adaptation of the Fanfiction Comic “the Story of Kresna’s Birth” in to Webtoon Format - I Putu Egga Putra Adnyana; I Gusti Made Budiarta; Nyoman Sila (Sean Institute, 2026)
Amidst the surge of numerous comics with contemporary plots and limitless story creations, it demands us to continuously adapt to the developments of the times in order to remain competitive in the creative world. One form of creativity is by combining creative elements from digital comics, such as webtoons, with famous traditional literary works that are rich in heroic elements, like the Mahabharata story. This study aims to: 1) describe the process of digitally creating